Da intimidade e do repouso: a imaginação simbólica do êxtase de Santa Teresa D'ávila - Herculano Filho, José (2022)
Teresa of Avila was a Spanish Catholic nun who lived in the 16th century and became famous for her devotional literature and mystical experiences, described in detail in her works, particularly in the Book of Her Life and the Interior Castle, the documentary basis of this research. The research problem investigated is the experiences of ecstasy as phenomena that foster the Teresian imagination, becoming resources of symbolic representations. It is assumed that Teresa of Jesus, through the experiences of ecstasies, resorted to symbols and images in the search for intimacy and rest. The fundamental aims are: to present the restorative dimensions of Teresian vital, psychosocial, anthropological and theophanic equilibrium; show the dynamism of the symbols between diurnal and nocturnal regimes and advocate the search for intimacy and rest in the garden and the dwellings, fostered by the ecstasies. To explore such propositions, we turn to the Human and Social Sciences, through Gilbert Durand's General Theory of the Imaginary. Durandian symbolic hermeneutics was used to identify the elements embedded in the narratives, in order to understand the contextualization of the Teresian life and, from the functions of symbolic imagination, understand her quest for the restoration of vital equilibrium, psychosocial stability, anthropological compensation and theophany; finally, the dynamics of imagination recurrent in the metaphors that appear the degrees of prayer between the watering of the garden and the interior of the dwellings are highlighted, a process by which the raptures in the respective works are triggered. As far as methodology is concerned, the research is bibliographic and field research, with visits to places mentioned in the research, such as Gotarrendura, in the province of Avila, the Adja River Bridge, the Convent of Our Lady of Grace, the Monastery of the Incarnation, in Avila and the Museum in Alba de Tormes, Spain. Regarding the purposes, it is exploratory; and for the means, it is descriptive, highlighting the dynamics of the textual language of the Carmelite nun, in the data collection and passages in her books; subsequently, the annotations and exploration of specific excerpts were carried out. The research is important because it contributes to interdisciplinary development, in Religions Sciences, Human and Social Sciences, especially on the question of ecstatic experiences, when approached from imagistic perspectives, emphasizing the linguistic style of Teresa of Jesus, who dedicated herself to a contemplative life. Therefore, the work favours academic research in spirituality, ascetic experience and Western theology, emphasising that the saint's legacy was restricted, over the centuries, only to the religious circle.